EVALUATION OF THE MANAGEMENT OF THE BRAZILIAN SCHOOL FEEDING PROGRAM IN GOIÁS MUNICIPALITIES: ANALYSIS OF DETERMINING FACTORS (REMUNOM, 2025)
Objectives: To analyze the factors influencing the municipal management of the Brazilian School Feeding Program (PNAE) in municipalities in the state of Goiás. Methods: A cross-sectional study conducted in 33 municipalities in the state of Goiás in 2018. Data were collected by trained researchers through the on-site administration of a semi-structured questionnaire with municipal PNAE managers. A validated evaluation matrix consisting of two dimensions (political-organizational and technical-operational), each with three sub-dimensions and a total of 22 indicators, was used. Associations were tested using Spearman's correlation (rs), with a significance level of p < 0.05. Results: In 69.7% of the municipalities, the management of PNAE was evaluated as "poor." It is noteworthy that the "resources" sub-dimension showed a positive correlation with intersectoral action (rs = 0.669; p < 0.01), food and nutritional monitoring (rs = 0.509; p < 0.05), and pedagogical action (rs = 0.539; p < 0.01). In addition, "intersectoral action" was associated with social control (rs = 0.427; p < 0.05), food and nutritional monitoring (rs = 0.502; p < 0.01), and pedagogical action (rs = 0.539; p < 0.01). Conclusion: Most of the evaluated municipalities face challenges in the management of PNAE, especially concerning human and financial resources, intersectoral action, and pedagogical activities. It emphasizes the need for improvements in these factors to enhance this important program for the nutrition and health of students.